Self-Disinfecting Paints with the Natural Antimicrobial Substances: Colophony and Curcumin - Querido, Micaela Machado (2022)
This article belongs to the Special Issue Nature Inspired Antibiotic Adjuvants to Face the Problem of Multidrug Resistance and Biofilm Infections